2016
DOI: 10.1002/bkcs.10767
|View full text |Cite
|
Sign up to set email alerts
|

Mild Approach for Non‐Catalytic Hydrogenation of Liquid Natural Rubber Using 2,4,6‐Trimethylbenzenesulfonyl Hydrazide as the Diimide Source

Abstract: This article reports an efficient, mild-temperature method for the hydrogenation of liquid natural rubber (LNR). The hydrogenation of LNR was studied using diimide generated in situ from the thermolysis of 2,4,6-trimethylbenzenesulfonyl hydrazide (MSH) in o-xylene at 100 C. The effects of reaction temperature, reaction time, solvent, and MSH/LNR weight ratio on the percentage of hydrogenation were evaluated. 1 H NMR analysis revealed that~80% hydrogenation was achieved with a weight ratio of MSH: LNR = 1:1 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Rasid et al had achieved the ratio of 1:1 for optimum MSH:LNR weight ratio. 22 Rasid et al also conducted an experiment with weight ratio of 2:1. It was revealed that the hydrogenation percentage had decreased.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rasid et al had achieved the ratio of 1:1 for optimum MSH:LNR weight ratio. 22 Rasid et al also conducted an experiment with weight ratio of 2:1. It was revealed that the hydrogenation percentage had decreased.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Rasid et al (2016) found that 100 ºC was the optimum reaction temperature in order to achieve a high percentage of hydrogenation. 22 During the experiments, the mixing speed was fixed at 650 rpm. Based on the studies that have been done, the range of each parameter was selected.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Catalytic hydrogenation requires high pressure autoclave and the presence of transition metal catalyst systems such as nickel, titanium, rhodium, ruthenium or palladium [8 -11]. On the other hand, non-catalytic hydrogenation method is more convenient because it only requires a simple apparatus preparation at atmospheric pressure and employed diimide intermediate from thermal decomposition of arylsulfonyl hydrazide [12]. Mahittikul et al reported an in situ hydrogenated natural rubber latex via thermolysis of p-toluenesulfonyl hydrazide (TSH) [13].…”
Section: -2506mentioning
confidence: 99%